The Olympic Games in post-socialist cities – a real goal or distant future? Case studies of Cracow and Almaty - Jastrząbek, Julia Anna (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2019)
The collapse of the Soviet Union has led to historical transitions in Central and Eastern Europe. The political and economic transformation in countries located in this world’s region has caused their dynamic socioeconomic development and more stable position on the international stage. Regarding the potential of hosting the Olympic Games as an opportunity for infrastructural im-provements, employment boost, and presentation of a positive image and traditions of a country, post-Soviet cities have entered the race for staging Olympic events. The main aim of this article is to analyse the bidding process for the 2022 Winter Olympic Games with an emphasis on case studies from two bidding cities with post-socialist history – Cracow and Almaty. Characteristic patterns and features of both cities’ bids, as well as diﬀerences between them are drawn, with conclusions on why these were unsuccessful. Cracow and Almaty’s bid paths in the 2022 Winter Olympics process were diﬀerent. Cracow pulled out from the race during the applicant phase because of referendum results: the city residents were against the Olympics, while Almaty reached the ﬁnal phase and lost to Beijing in ﬁnal voting. It seems that post-socialist countries still have a weaker bargaining position in the bidding process than candidates with advanced and estab-lished economies.
Keywords: Winter Olympic Games; mega-events; post-socialist cities; political economy